The Assignment of Investment Treaty Claims: Mapping the Principles. (17th August 2018) - Goh, Nelson
Abstract: Recent investment law scholarship has focused on the legitimacy of corporate restructuring to obtain treaty protection. Less scrutiny has however been directed to the assignment of investment treaty claims. What principles govern the transferability of an investment claim? Investment tribunals have differing views on the validity of assigned claims: some have suggested that such claims are unique and cannot be openly transferrable as financial instruments are, while others have acknowledged that in principle, claims are assignable although they may face jurisdictional defects. This article seeks to elucidate the rules from the prevailing but limited corpus of decisions on the topic. It submits that there should be no general prohibition against the assignment of investment treaty claims, and instead posits a paradigm which prevents abuse but is consistent with the object and purpose of investment treaties to attract foreign investment.